2021
DOI: 10.3389/fimmu.2021.734471
|View full text |Cite
|
Sign up to set email alerts
|

Epstein Barr Virus: Development of Vaccines and Immune Cell Therapy for EBV-Associated Diseases

Abstract: Epstein-Barr virus (EBV) is the first human tumor virus discovered and is strongly implicated in the etiology of multiple lymphoid and epithelial cancers. Each year EBV associated cancers account for over 200,000 new cases of cancer and cause 150,000 deaths world-wide. EBV is also the primary cause of infectious mononucleosis, and up to 70% of adolescents and young adults in developed countries suffer from infectious mononucleosis. In addition, EBV has been shown to play a critical role in the pathogenesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
103
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 220 publications
(296 reference statements)
0
103
0
1
Order By: Relevance
“…The prognosis of Epstein–Barr virus infection in UC was less paid attention to 45 . In this study, the KEGG pathways results indicated that more studies of the Epstein–Barr virus infection pathway in UC could be conducted 46 . Particularly, IBD patients have a higher risk to develop autoimmune and inflammatory diseases, such as rheumatoid arthritis 47 .…”
Section: Discussionmentioning
confidence: 79%
“…The prognosis of Epstein–Barr virus infection in UC was less paid attention to 45 . In this study, the KEGG pathways results indicated that more studies of the Epstein–Barr virus infection pathway in UC could be conducted 46 . Particularly, IBD patients have a higher risk to develop autoimmune and inflammatory diseases, such as rheumatoid arthritis 47 .…”
Section: Discussionmentioning
confidence: 79%
“…Adoptive T cell therapy has been successfully applied for treating patients with EBV-associated PTLD by reconstituting host cellular immunity against the disease. The first clinical trial of adoptive T cell therapy showed that infusion of donor-derived EBV-specific T cells (EBVSTs) into patients with allogeneic hematopoietic stem cell transplantation (HSCT) induced complete regression in all five patients, but graft-versus-host disease developed [ 153 ]. Later, in vitro expanded donor-derived or autologous EBVSTs in phase I clinical trials were proven effective in the prevention and treatment of PTLD in HSCT or solid organ transplantation patients with minimal alloreactivity [ 154 , 155 ].…”
Section: Landscape Of Different Ebv-associated Malignanciesmentioning
confidence: 99%
“…In addition, most therapeutic EBV vaccines have been focused on patients with NPC, and early clinical trials were done with DC-based EBV vaccines and recombinant viral vector vaccines [ 192 , 193 ]. Although the therapeutic EBV vaccines have shown increasing T cell responses in patients with NPC, future studies remain to be done to overcome the limited antigen epitopes delivered by DC-based EBV vaccines and the decreased antiviral vector immune responses after repeated immunizations [ 153 , 194 ].…”
Section: Landscape Of Different Ebv-associated Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…A small proportion of people infected with EBV present with infectious mononucleosis, which can cause persistent fatigue for up to 6 months and lead to serious neurological, hematological or hepatic complications. EBV was also the first human oncovirus to be identified and it is closely associated with several lymphomas and epithelial cancers especially in immunocompromised individuals, such as Burkitt’s lymphoma, Hodgkin’s lymphoma and nasopharyngeal carcinoma (NPC) ( Cui and Snapper, 2021 ). In general, the utilizing of existing antiviral compounds is limited by toxic side effects, poor oral bioavailability and the risk of the emergence of resistant viral strains.…”
Section: Antiviral Activity Of Emodinmentioning
confidence: 99%